increasing by 3 inches every hour.
How long until the snowfall in both cities is equal?
A. 1 hour and 20 minutes
B. 1 hour and 33 minutes
C. 45 minutes
D. 1 hour 15 minutes
Answer:
Therefore, after 1 hour and 20 minutes, the snowfall in both cities was equal to 13 inch.
Step-by-step explanation:
Calculating the depth of First Town:
First town has accumulated 5 inches of snow.
As the depth is increasing by 6 inches every hour
so the depth increase after 45 minutes i.e. 3/4 hour = 4.5 inch
so
After 45 minutes
Snow level of First town after 45 min = 4.5 + 5 = 9.5 inch
After 1 hour
Snow level of First town after 1 hour = 5 + 6 = 11 inch
After 1 hour and 20 minutes
5 + 6 + 2 = 13 inch ∵ If 6 inch per hour, then 2 inch in 20 min
Calculating the depth of Second Town:
Second town has accumulated 9 inches of snow.
As the depth is increasing by 3 inches every hour.
so the depth increase after 45 minutes i.e. 3/4 hour = 2.25 inch
so
After 45 minutes
Snow level of Second town after 45 min = 9 + 2.25 = 11.25 inch
After 1 hour
Snow level of Second town after 1 hour = 9 + 3 = 12 inch
After 1 hour and 20 minutes
Snow level of Second town after 1 hour and 20 minutes
9 + 3 + 1 = 13 inch ∵ If 3 inch per hour, then 1 inch in 20 min
From the above observation, it is clear that after 1 hour and 20 minutes the snowfall in both cities was equal.
Therefore, after 1 hour and 20 minutes, the snowfall in both cities was equal to 13 inch.
An equation that represents the value of the circumference, C, of a circle with a diameter of 48 feet is C=2π×24.
The circumference is the length of any great circle, the intersection of the sphere with any plane passing through its Centre. A meridian is any great circle passing through a point designated a pole.
Given that, a circle with a diameter of 48 feet.
Here, radius = Diameter/2
Radius = 48/2 = 24 feet
We know that, the circumference of a circle is 2πr.
Now,
C=2π×24
C=2×3.14×24
C=150.72 feet
Therefore, the circumference of a circle is 150.72 feet.
To learn more about the circumference visit:
#SPJ3
Answer:
x<-3
Step-by-step explanation:
adding 3x on both sides,
4>13+3x
subtracting 13 from both sides,
4-13>3x
-9>3x
dividing both the sides by 3,
-3>x
therefore solution: x<-3